On the direct nucleation and growth of ferrite and cementite without austenite. (15th January 2015) - Fillon, A.; Sauvage, X.; Lawrence, B.; Sinclair, C.; Perez, M.; Weck, A.; Cantergiani, E.; Epicier, T.; Scott, C.P.
Abstract : The direct nucleation and growth of ferrite and cementite has been investigated in an Fe–C metallic glass using X-ray diffraction, transmission electron microscopy and atom probe tomography. The nucleation and growth proceeds via primary crystallization of ferrite, without the formation of austenite. There is no carbon gradient at ferrite/amorphous interfaces, indicating that the transformation rate is controlled by the low mobility of these interfaces compared to the mobility of C atoms. A thermodynamic description is proposed to explain the delayed nucleation of cementite.